A Pragmatic Study Shows Failure of Dental Composite Fillings Is Genetically Determined: A Contribution to the Discussion on Dental Amalgams - Vieira, Alexandre R.; Silva, Marília B.; Souza, Kesia K. A.; Filho, Arnôldo V. A.; Rosenblatt, Aronita; Modesto, Adriana (Frontiers in Medicine, 2017)
Composite resins for posterior tooth restorations have become a viable alternative to dental amalgam. Failures sometimes cannot be easily explained and we hypothesize a genetic component may influence longevity of restorations. We aimed to determine if there is any evidence for a difference in the performance of amalgams versus composite resin in extensive posterior restorations. We also aimed to determine if risk factors such as age, sex, smoking tobacco, alcohol drinking, diabetes status, and periodontal health status may have a role in the failures of extensive anterior composite restorations. Finally, we investigated if genetic variation in matrix metalloproteinases (MMPs) that are present in the mineralized dentin is associated with failure of composite resin. The data used to perform this research were obtained from the Dental Registry and DNA Repository project after screening 4,856 patients. All restorations were evaluated at times of 1, 2 and 5 years after the restoration placement. 6,266 amalgam and 2,010 composite restorations were analyzed in a total of 807 patients in a period of approximately 10 years (period corresponding to the database existence). An additional 443 extensive direct composite resin restorations in anterior teeth were also studied. Failure rates of amalgam and composite restorations are similar, and by the end of 5 years, composites outperformed amalgams slightly. Failures of anterior composite restorations occurred more often in males who smoked tobacco (p=0.05), despite a similar number of females and males that smoked tobacco in the sample (116 individuals smoked tobacco, 54 females and 62 males). Alcohol drinking increased failure rate within two years (p=0.03). We found a statistically significant association between MMP2 rs9923304 and failure of composite restorations (p=0.007). Composite resins can replace amalgam restorations. Smoking tobacco and drinking alcohol will increase the chance of restoration failure.